A comparison of Motivational Traits in Skilled and Novice Athletes in Individual and Team Sports in Some Selected Sport Fields - Fazlolah Bagherzadeh; Masoumeh Hadiyan; Mehdi Ghafouri; Arezou Azadi (University of Tehran, 2017)
Motivation is one of those factors affecting the success and quality of athletic performance. However, limited research has been conducted on the motivational traits of Iranian athletes. This study aimed at describing the motivational traits of skilled and novice athletes of team and individual sports in some selected sports fields. Players of national teams of the individual sports of karate, taekwondo, fencing, badminton, sailing and team sports of basketball, volleyball, Dragon boat, handball and futsal were purposively selected as the population of skilled athletes and 60 athletes were randomly selected from all above selected sports fields from some selected provinces as the sample of novice athletes. Data from the Sport Attitudes Inventory (SAI) were classified according to team and individual sports and players were classified according to novice and skilled levels and data were analyzed using descriptive statistics. Inferential statistical results of ANOVA showed that competitive motivation was significantly higher in skilled and novice athletes of individual sports than team sports and it was higher in skilled athletes than novice athletes (P<0.05).